SISTEM INFORMASI PELAYANAN KELUARGA BERENCANA KAMPUNG KB BERBASIS WEB PADA DINAS PENGENDALIAN PENDUDUK DAN KB KABUPATEN ALOR - Maleimakuni, Hans Julianus; Payong, Yohanes (HOAQ (High Education of Organization Archive Quality) : Jurnal Teknologi Informasi, 2020)
In the success of the KKBPK program, competent program managers are needed, and can utilize technology properly to support the implementation of the program, especially in managing a complete, structured, and transparent information system to service officers and also the community so that the need for information is needed by every party involved. interested parties can be fulfilled properly, completely, quickly. The purpose of this research is to build a Web-Based Information System for Family Planning Services at the Alor District Family Planning and Family Planning Service to make it easier for family planning field officers (PLKB) to convey all information and activities for family planning services. The method used for designing this system is the waterfall method. The results to be achieved through the Web-Based Kampung KB Family Planning Service Information System are to make it easier for family planning field officers to convey all information and family planning service activities carried out to all service users, both service officers and the general public.